1990
DOI: 10.1021/tx00014a004
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus-32 postlabeling measurement of adenine N-1-oxide in cellular DNA exposed to hydrogen peroxide

Abstract: A 32P-postlabeling assay has been developed for monitoring the formation within DNA of adenine N-1-oxide, the specific H2O2-mediated oxidation product under nonradical conditions. This has required the chemical synthesis of both 2'-deoxyadenosine N-1-oxide 3'-monophosphate and 2'-deoxyadenosine N-1-oxide 5'-monophosphate, the substrate and the product of polynucleotide kinase mediated phosphorylation. Isolation of the substrate from the other nucleotides was found to be necessary in order to improve the rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(15 citation statements)
references
References 44 publications
(74 reference statements)
1
14
0
Order By: Relevance
“…This is in agreement with previous measurements of oligonucleotide strand breaks when an alkaline elution assay was performed after extraction of the DNA from mammalian cells and its subsequent incubation with the E. coli FPG protein (72)(73)(74). The level of 8- [32P]-postlabeling approach was already applied for the determination of 2'deoxyadenosine N-1 oxide and 5-(hydroxymethyl)-2'-deoxyuridine (79,80). Another example of overestimation of the measurement level of 8-oxodGuo is provided by an immunoslot blot assay (81).…”
supporting
confidence: 88%
“…This is in agreement with previous measurements of oligonucleotide strand breaks when an alkaline elution assay was performed after extraction of the DNA from mammalian cells and its subsequent incubation with the E. coli FPG protein (72)(73)(74). The level of 8- [32P]-postlabeling approach was already applied for the determination of 2'deoxyadenosine N-1 oxide and 5-(hydroxymethyl)-2'-deoxyuridine (79,80). Another example of overestimation of the measurement level of 8-oxodGuo is provided by an immunoslot blot assay (81).…”
supporting
confidence: 88%
“…3 C and D). The conditions (16). Moreover, the lesion was not removed by treatment of '-yirradiated DNA with alkali or E. coli endonuclease IV, demonstrating that it was not an abasic site (data not shown).…”
mentioning
confidence: 87%
“…It is a major non-radical species produced by a series of metabolic processes of non-reactive superoxide anions, and is widely present in living cells ( 19–21 ). The main products obtained by the oxidation of cytosine and adenine bases with hydrogen peroxide are cytosine N -oxide (C o ) and adenine N -oxide (A o ) derivatives, respectively ( Figure 1 ) ( 22–32 ).
Figure 1.
…”
Section: Introductionmentioning
confidence: 99%
“…Cadet reported that adenine N 1 -oxide is formed using hydrogen peroxide as a predominant ionic DNA base damage under non-radical conditions ( 29 ). 2′-Deoxyadenosine N 1 -oxide (3.2/10 6 bases) was detected to be present in the DNA of the untreated wild-type Proteus mirabilis cells ( 28 ). When they were exposed to nonlethal level of 10 mM hydrogen peroxide, the amount of this modified nucleoside was found to be 8.3 times higher than in the untreated cells ( 28 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation